You are on page 1of 6

# FSC-I / Ex 5.

3 - 1

## mathcity.org Exercise 5.3 (Solutions)

Textbook of Algebra and Trigonometry for Class XI
Merging man and maths Available online @ http://www.mathcity.org, Version: 1.0.0

9x − 7
Question # 1
( x 2 + 1)( x + 3)
Resolving it into partial fraction.
9x − 7 Ax + B C
= 2 +
( x + 1)( x + 3) ( x + 1) ( x + 3)
2

## Multiplying both sides by ( x 2 + 1)( x + 3) .

9 x − 7 = ( Ax + B)( x + 3) + C ( x2 + 1) ............ (i )
Put x + 3 = 0 ⇒ x = −3 in equation (i).
9(−3) − 7 = ( A(−3) + B )( 0 ) + C ( (−3) 2 + 1) ⇒ − 27 − 7 = 0 + C ( 9 + 1)
34 17
⇒ − 34 = 10C ⇒ C =− ⇒ C =−
10 5
Now equation (i) can be written as
9 x − 7 = A ( x 2 + 3x ) + B ( x + 3) + C ( x 2 + 1)
Comparing the coefficients of x 2 , x and x 0 .
0 = A + C …………….…... (ii)
9 = 3A + B ……………..… (iii)
−7 = + 3B + C …………...…. (iv)
Putting value of C in equation (ii)
17 17
0= A− ⇒ A =
5 5
Now putting value of A in equation (iii)
 17  51 51 6
9 = 3  + B ⇒ 9= +B ⇒ 9 − = B ⇒ B=−
 5 5 5 5
Hence
17 6 17
x− −
9x − 7
= 52 5 + 5
( x + 1)( x + 3)
2
x +1 ( x + 3)
17 x − 6 17
17 x − 6 17
= 5 − 5 = − Answer
x2 + 1 ( x + 3) 5( x 2 + 1) 5( x + 3)

1
Question # 2
( x + 1)( x + 1)
2

Now Consider
1 Ax + B C
= 2 +
( x + 1)( x + 1)
2
x +1 x +1
Multiplying both sides by ( x 2 + 1)( x + 1) .
1 = ( Ax + B)( x + 1) + C ( x 2 + 1)................ (i )
Put x + 1 = 0 ⇒ x = −1 in equation (i)

1 = 0 + C ( (−1) 2 + 1)
1
⇒ 1 = 2C ⇒ C =
2
Now eq. (i) can be written as
FSC-I / Ex 5.3 - 2

1 = A( x 2 + x) + B ( x + 1) + C ( x 2 + 1)
Comparing the coefficients of x 2 , x and x 0 .
0 = A + C …………….…. (ii)
0 = A + B ………………. (iii)
1 = A + C ………………. (iv)
Putting value of C in equation (ii)
1 1
0= A+ ⇒ A = −
2 2
Putting value of A in equation (iii)
1 1
0=− +B ⇒ B=
2 2
1 1 1 −x + 1 1
− x+
1
Hence = 22 2 + 2 = 2 + 2
( x + 1)( x + 1)
2
x +1 x +1 x +1 x +1 2

−x +1 1 1− x 1
2( x 2 + 1) 2( x + 1) 2( x 2 + 1) 2( x + 1)

3x + 7
Question # 3
( x + 4)( x + 3)
2

## Resolving it into partial fraction.

3x + 7 Ax + B C
= +
( x 2 + 4)( x + 3) x 2 + 4 x+3
 Now do yourself , you will get 
 
 A = 2 13 , B = 13 and C = − 2 13
33


x 2 + 15
Question # 4
( x 2 + 2 x + 5)( x − 1)
Resolving it into partial fraction.
x 2 + 15 Ax + B C
= 2 +
( x + 2 x + 5)( x − 1) x + 2 x + 5 x − 1
2

⇒ x 2 + 15 = ( Ax + B)( x − 1) + C ( x 2 + 2 x + 5).............. (i )
Put x − 1 = 0 ⇒ x = 1 in equation (i)
(1)2 + 15 = ( A(1) + B ) (0) + C ( (1)2 + 2(1) + 5 ) ⇒ 1 + 15 = 0 + C (1 + 2 + 5)
16
⇒ 16 = 8C ⇒ =C ⇒ C = 2
8
Now equation (i) can be written as
x 2 + 15 = A ( x 2 − x ) + B ( x − 1) + C ( x 2 + 2 x + 5)
Comparing the coefficients of x 2 , x and x 0 .
1 = A + C …………..………. (ii)
0 = − A + B + 2C ………….. (iii)
15 = − B + 5C ………….….. (iv)
Putting value of C in equation (ii).
1 = A + 2 ⇒ 1− 2 = A ⇒ A = − 1
Putting value of A and C in equation (iii)
FSC-I / Ex 5.3 - 3

## 0 = − (−1) + B + 2(2) ⇒ 0 =1+ B + 4 ⇒ 0 = B + 5 ⇒ B =−5

x 2 + 15 (−1) x − 5 2
Hence = 2 +
( x + 2 x + 5)( x − 1) x + 2 x + 5 x − 1
2

−x − 5 2
x + 2x + 5 x −1

x2
Question # 5
( x 2 + 4)( x + 2)
Resolving it into partial fraction.
x2 Ax + B C
= 2 +
( x + 4)( x + 2)
2
x +4 x+2
 Now do yourself , you will get 
 1 , B = − 1 and C = − 1 
=
 2 
A
2

x2 + 1 x2 + 1
Question # 6 = Q x 3 + 1 = ( x + 1)( x 2 − x + 1)
x3 + 1 ( x + 1)( x 2 − x + 1)
Now consider
x2 + 1 A Bx + C
= +
( x + 1)( x 2 − x + 1) x + 1 x 2 − x + 1
 Now do yourself , you will get 
 
 A = 3 , B = 3 and C = 3
2 1 1


x2 + 2x + 2
Question # 7
( x 2 + 3)( x + 1)( x − 1)
Consider
x2 + 2 x + 2 Ax + B C D
= 2 + +
( x + 3)( x + 1)( x − 1)
2
x +3 x +1 x −1
⇒ x 2 + 2 x + 2 = ( Ax + B)( x + 1)( x − 1) + C ( x 2 + 3)( x −1) + D ( x 2 + 3)( x + 1)............. (i )
Put x + 1 = 0 ⇒ x = −1 in equation (i)
(−1)2 + 2(−1) + 2 = 0 + C ( (−1)2 + 3 ) ( (−1) −1) + 0 ⇒ 1 − 2 + 2 = C ( 4 )( −2 )
1
⇒ 1 = − 8C ⇒ C=−
8
Now put x − 1 = 0 ⇒ x = 1 in equation (i)
⇒ (1)2 + 2(1) + 2 = 0 + 0 + D ( (1)2 + 3) ( (1) + 1) ⇒ 1 + 2 + 2 = D ( 4 )( 2 )
5
⇒ 5= 8D ⇒ D=
8
Equation (i) can be written as
x 2 + 2 x + 2 = ( Ax + B)( x 2 − 1) + C ( x 3 − x 2 + 3x − 3) + D ( x 3 + x 2 + 3x + 3)
⇒ x 2 + 2 x + 2 = A( x 3 − x) + B ( x 2 − 1) + C ( x3 − x 2 + 3x − 3) + D ( x 3 + x 2 + 3x + 3)
Comparing the coefficients of x 3 , x 2 , x and x 0 .
0 = A + C + D ……………...…. (ii)
1= B − C + D ……………….…. (iii)
2 = − A + 3C + 3D ……………. (iv)
FSC-I / Ex 5.3 - 4

2 = − B − 3C + 3D ………….…. (v)
Putting values of C and D in (ii)
1 5 1 1
0= A− + ⇒ 0= A+ ⇒ A=−
8 8 2 2
Putting values of C and D in (iii)
 1 5 1 5 3
1= B −−  + ⇒ 1= B + + ⇒ 1= B +
 8 8 8 8 4
3 1
⇒ 1− =B ⇒ B=
4 4
Hence
1 1 1 5
− x+ −
x + 2x + 2
2
= 22 4 + 8 + 8
( x + 3)( x + 1)( x − 1)
2
x +3 x +1 x −1
−2 x + 1 1 5

−2 x + 1 −1 5
= 4 + 8 + 8 = + +
x2 + 3 x +1 x −1 4( x 2 + 3) 8( x + 1) 8( x − 1)
1 − 2x 1 5
4( x + 3)
2
8( x + 1) 8( x − 1)

1
Question # 8
( x − 1)2 ( x 2 + 2)
Resolving it into partial fraction.
1 A B Cx+D
= + + 2
( x − 1) ( x + 2) x − 1 ( x − 1)
2 2 2
x +2
⇒ 1 = A ( x − 1)( x 2 + 2) + B ( x 2 + 2) + (C x + D)( x − 1)2 ............. (i )
Put x − 1 = 0 ⇒ x = 1 in equation (i)

1 = 0 + B ( (1) 2 + 2 ) + 0
1
⇒ 1 = 3B ⇒ B=
3
Now equation (i) can be written as
1 = A ( x 3 − x 2 + 2 x − 2) + B ( x 2 + 2) + (C x + D)( x 2 − 2 x + 1)
⇒ 1 = A ( x3 − x 2 + 2 x − 2) + B ( x 2 + 2) + C ( x3 − 2 x 2 + x ) + D ( x 2 − 2 x + 1)
Comparing the coefficients of x 3 , x 2 , x and x 0 .
0 = A + C ……………………. (ii)
0 = − A + B − 2C + D …..…….. (iii)
0 = 2 A + C − 2 D …………..… (iv)
1 = −2 A + 2 B + D ……………. (v)
Multiplying eq. (iii) by 2 and adding in (iv)
0 = −2 A + 2 B − 4C + 2 D
0 = 2A + C − 2D
0= 2 B − 3C
Putting value of B in above
1 2 2 2
0 = 2   − 3C ⇒ 0 = − 3C ⇒ 3C = ⇒ C=
 3 3 3 9
Putting value of C in eq. (ii)
2 2
0= A+ ⇒ A=−
9 9
FSC-I / Ex 5.3 - 5

## Putting value of A and B in eq. (v)

 2 1 4 2 4 2 1
1 = −2  −  + 2   + D ⇒ 1 = + + D ⇒ 1 − − = D ⇒ D=−
 9 3 9 3 9 3 9
Hence
1
=
−2
9 +
1
3
2 x+ − 1
+ 9 2 9 ( ) ( )
( x − 1) ( x + 2) x − 1 ( x − 1)
2 2 2
x +2
2x − 1
−2 1
−2 1 2x − 1
= 9+ 3 + 9 = + +
x − 1 ( x − 1) 2
x +2
2
9( x − 1) 3( x − 1) 2
9( x 2 + 2)

x4
Question # 9 −1
1 − x4
1 1 1 − x 4 x4
= −1 + = − 1 +
1 − x4 (1 − x 2 )(1 + x 2 ) x 4 −1
− +
1 1
= −1 +
(1 − x)(1 + x)(1 + x 2 )

Now consider
1 A B Cx + D
= + +
(1 − x)(1 + x )(1 + x ) 1 − x 1 + x 1 + x 2
2

##  Now find values of A, B, C and D yourself . 

 
 You will get A = 4 , B = 4 , C = 0 and D = 2
1 1 1

So
1
1 1 (0) x + 12
= 4 + 4 +
(1 − x)(1 + x )(1 + x 2 ) 1 − x 1 + x 1 + x2
1 1 1
= + +
4(1 − x) 4(1 + x) 2(1 + x 2 )
Hence
x4 1 1 1
= −1 + + + Answer
1− x 4
4(1 − x) 4(1 + x ) 2(1 + x 2 )

x2 − 2 x + 3
Question # 10 Q x 4 + x 2 + 1 = x4 + 2 x 2 + 1 − x 2
x 4 + x2 + 1
= ( x 2 + 1) 2 − x 2
x − 2x + 3
2
= ( x 2 + 1 + x )( x 2 + 1 − x)
= 2
( x + x + 1)( x − x + 1)
2
= ( x 2 + x + 1)( x 2 − x + 1)
Now Consider
x2 − 2 x + 3 Ax + B Cx+D
= +
( x 2 + x + 1)( x 2 − x + 1) x 2 + x + 1 x 2 − x + 1
⇒ x 2 − 2 x + 3 = ( Ax + B)( x 2 − x + 1) + (Cx + D)( x 2 + x + 1).............. (i )
⇒ x 2 − 2 x + 3 = A( x 3 − x 2 + x ) + B ( x 2 − x + 1) + C ( x3 + x 2 + x) + D( x 2 + x + 1)
Comparing the coefficients of x 3 , x 2 , x and x 0 .
0 = A + C ……………………..… (ii)
1 = − A + B + C + D ……………. (iii)
−2 = A − B + C + D …………...… (iv)
FSC-I / Ex 5.3 - 6

3 = B + D …………………….... (v)
Subtracting (ii) and (iv)
0= A +C
− 2 = A− B + C + D
+ − + − −
2= B −D
⇒ 2 = B − D …………… (vi)
3= B+ D
2=B−D
5 = 2B
5
⇒ B=
2
Putting value of B in (v)
5 5 1
3= + D ⇒3− = D ⇒ D=
2 2 2
Putting value of B and D in (iii)
5 1 5 1
1= − A + + C + ⇒ 1− − =− A + C
2 2 2 2
⇒ − 2 = − A + C ……………. (vii)
0= A+C
−2 = − A + C
−2 = 2C ⇒ C = −1
Putting value of C in equation (ii)
0 = A −1 ⇒ A=1
Hence
5 1
(1) x + (−1) x +
x − 2x + 3
2
= 2 2 + 2
( x + x + 1)( x − x + 1) x + x + 1 x − x + 1
2 2 2

2x + 5 −2 x + 1

= 2 + 2
x + x +1
2
x − x +1
2

2x + 5 −2 x + 1
= +
2( x 2 + x + 1) 2( x 2 − x + 1)
2x + 5 1 − 2x